2021
DOI: 10.3389/fpsyt.2021.625247
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Symptoms of Depression and Anxiety Using Smartphone and Wearable Data

Abstract: Background: Depression and anxiety are leading causes of disability worldwide but often remain undetected and untreated. Smartphone and wearable devices may offer a unique source of data to detect moment by moment changes in risk factors associated with mental disorders that overcome many of the limitations of traditional screening methods.Objective: The current study aimed to explore the extent to which data from smartphone and wearable devices could predict symptoms of depression and anxiety.Methods: A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
106
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 82 publications
1
106
0
1
Order By: Relevance
“…Nevertheless, both the correlation findings and the feature importance analysis in the prediction models clearly showed that participants’ phone screen (lock and unlock) behaviors, such as routinely and randomly locking and unlocking phone screen, and internet connectivity behaviors played the most important role in predicting their depression state. The findings in this study are also supported by prior research that investigated the relationship between screen interactions and mental health [ 3 , 27 , 28 , 33 ]. Passively sensed participants’ smartphone screen interaction (ie, on and off states) behavior was demonstrated to be an important predictor of mental health [ 27 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, both the correlation findings and the feature importance analysis in the prediction models clearly showed that participants’ phone screen (lock and unlock) behaviors, such as routinely and randomly locking and unlocking phone screen, and internet connectivity behaviors played the most important role in predicting their depression state. The findings in this study are also supported by prior research that investigated the relationship between screen interactions and mental health [ 3 , 27 , 28 , 33 ]. Passively sensed participants’ smartphone screen interaction (ie, on and off states) behavior was demonstrated to be an important predictor of mental health [ 27 ].…”
Section: Discussionsupporting
confidence: 88%
“…Instrumenting smartphones and wearables to capture in situ, fine-grained, and moment-by-moment data sets with sensing apps [ 20 - 24 ] has made it possible to passively collect data sets in naturalistic settings. Inherent in these data sets are behavioral patterns: routines, rhythms, activities, and interactions that are useful in complementing traditional depression assessment methods, in studying the mental health of individuals, and in developing timely mental health interventions [ 14 , 22 , 25 - 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented the potential for using EWDs in continuous patient symptom monitoring, longitudinal data collection, supportive self-care, and early detection of relapse among people with mental illness ( 16 ). However, the role of EWDs in stimulating physical activity in those with mental illness remains to be proven.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep latency refers to the amount of time it takes to fall asleep, whereas sleep efficiency measures the percentage of time spent asleep while in bed [41,42]. The effect of TRE on sleep latency and efficiency was evaluated in four trials [22,23,26,27].…”
Section: Sleep Latency and Sleep Efficiencymentioning
confidence: 99%